2019
DOI: 10.1093/jas/sky460
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophage functions during the transition phase to active immunity in calves

Abstract: The article "Alveolar macrophage functions during the transition phase to active immunity in calves" by Bertagnon et al [doi: 10.1093/jas/ sky261] contained incorrect funding information, which has now been corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…CD14 is one of the well-known lipopolysaccharide (LPS) receptors and is highly expressed on macrophages and monocytes [ 17 ]. Previous studies on bovine BALF have used CD14 expression to define alveolar macrophages and assess functional maturation [ 4 , 6 ]. However, human and experimental animal studies have shown that phenotypic markers of alveolar macrophages are very different from those of monocytes and other macrophages, and the expression of CD14 is known to be low as in our present report [ 5 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD14 is one of the well-known lipopolysaccharide (LPS) receptors and is highly expressed on macrophages and monocytes [ 17 ]. Previous studies on bovine BALF have used CD14 expression to define alveolar macrophages and assess functional maturation [ 4 , 6 ]. However, human and experimental animal studies have shown that phenotypic markers of alveolar macrophages are very different from those of monocytes and other macrophages, and the expression of CD14 is known to be low as in our present report [ 5 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since this study was conducted only on calves (15–60-days old), a further study is needed to determine whether the present method can be directly applied to adult cattle and other breeds. A report suggests that the maturation of bovine alveolar macrophages is not completed until the age of 6 months [ 6 ], and hence, a longer-term study will be necessary.…”
Section: Discussionmentioning
confidence: 99%